2020
DOI: 10.3389/fimmu.2020.571759
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fracture Leads to Transitory Immune Imprint in Older Patients

Abstract: Background: Hip fracture (HF) is common in the geriatric population and is associated with a poor vital and functional prognosis which could be impacted by immunological changes. The objective here is to decipher immune changes occurring in the 1st days following HF and determine how phenotype, function, and regulation of innate and adaptive compartments adapt during acute stress event. Methods: We included HF patients, aged over 75 years. For each patient, blood samples were taken at five different timepoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Among them, monocytes are of particular interest because they express inflammatory genes mainly in PBMCs [ 34 , 35 ]. In elderly hip fracture patients, the frequencies of postoperative monocyte increased significantly within 24 h, gradually returning to normal level by day 7, which is consistent with other findings [ 36 ]. C-Mono2 subsets exhibit high expression levels of S100 family genes, which are predominantly expressed by neutrophils and monocytes and play a crucial role in inflammation development [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among them, monocytes are of particular interest because they express inflammatory genes mainly in PBMCs [ 34 , 35 ]. In elderly hip fracture patients, the frequencies of postoperative monocyte increased significantly within 24 h, gradually returning to normal level by day 7, which is consistent with other findings [ 36 ]. C-Mono2 subsets exhibit high expression levels of S100 family genes, which are predominantly expressed by neutrophils and monocytes and play a crucial role in inflammation development [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…This cohort was described previously. 9 For immunosenescence status comparison, 5 young donors (25< age <40) from blood transfusion center (Etablissement Français du Sang) were also included (CTRLy).…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 8 The trauma induced by HF is also associated with additional immunological changes such as a transient pro-inflammatory phenotype of the innate compartment and immunosuppressive profile of the adaptative compartment. 9 These changes may participate in the poor medical outcome post-HF in some of these patients. A comprehensive investigation of the induced immune-alterations post-stress would open avenues for the development of immunotherapies enabling the restoration of immune homeostasis, especially in the situation of trauma such as HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced quality of life, subsequent secondary fracture and heavy financial burdens make HF an increasingly important public health concern for elderly individuals. Healthy older individuals experience higher levels of stress than young adults, and HF in elderly patients is associated with complicated immunological changes, including changes in innate proinflammatory phenotypes and adaptive immunosuppressive responses (Vallet et al, 2020). In addition, studies have shown that geriatric HF patients have a reduced ability to exhibit an effective antimicrobial immune response and that these immunological effects can be sustained until 7 days after surgery (Sutherland et al, 2015).…”
Section: Introductionmentioning
confidence: 99%